Parasupersymmetric quantum mechanics of arbitrary order withN parasupercharges - Symenoh, Z. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
Parasupersymmetric quantum mechanics is generalized to the case of an arbitrary number of parasuperchanrges N and the order of paraquantization p. We show that parasuperpotentials can be explicitly expressed via a single arbitrary function.